The Building the Character of a Digital Native Generation: A Prophetic Approach Through Parents and Teachers: Membangun Karakter Generasi Digital: Pendekatan Profetik Melalui Peran Orang Tua dan Guru - Mariyani, Mariyani; Rahmawati, Rahmawati; Alif Al Ghifari, M (Civic Education Perspective Journal, 2025)
This study discusses the importance of prophetic approaches in building the character of the digital native generation through the role of parents and teachers. The prophetic approach integrates prophetic values such as humanization, liberation, and transcendence in education, helping children develop high morality, empathy, and critical thinking skills. This study uses a literature study design to examine prophetic approaches in character education, researchers collect and analyze a variety of relevant literature sources, including books, journal articles, and research reports. The results were obtained that collaboration between parents and teachers is essential to ensure consistency in character formation, both at home and at school. With this holistic prophetic approach, the digital native generation can grow up to be individuals with strong character, able to use technology wisely, and contribute positively to society.